The effects of a season-long imagery intervention on curling performance: A mixed-methods evaluation - Westlund, N.; Hall, C. R. (Journal of Exercise, Movement, and Sport, 2015)
The purpose of this study was to conduct an imagery intervention that spanned an entire competitive curling season. A junior women's curling team, consisting of four members (Mage = 17.50, SD = 1.00), participated in the study. Semi-structured interviews were conducted at the start and end of the team's competitive curling season based on Munroe and colleagues' (2000) 4Ws of imagery use to determine how the athletes used imagery in curling and how it changed following the intervention. Athletes practiced audio-recorded imagery scripts throughout the season that were developed in collaboration with the team's coach to match the team's changing needs. Statistical examination of athletes' imagery use scores revealed that the use of cognitive general imagery and motivational general-mastery imagery increased from pre- to post-intervention (p < .05). At pre-intervention, athletes reported using imagery for all five functions, with cognitive general imagery and cognitive specific imagery being mentioned most often. At post-intervention, athletes reported using only four imagery functions, with cognitive specific imagery and motivational general-mastery imagery being mentioned most often. Athletes also discussed using imagery more frequently as a result of the intervention, as well as being able to identify their preferences (e.g., modalities and perspectives) when it came to using imagery. Based on the quantitative and qualitative results, athletes learned to target their imagery use to their specific needs throughout the intervention, compared to using it more generally at the start of the season. This has important implications for applied practitioners who are working with high-level athletes.